Television at large in South Asia/ edited by Aswin Punathambekar and Shanti Kumar - "Punathambekar, Aswin (ed.);Shanti Kumar (ed.)" (New Delhi, 2014)
This book explores the empirical and theoretical significance of understanding television as a dynamic technology, a creative industry, and a vibrant cultural form that is "at large" in South Asia. Bringing together prominent scholars who have shaped television studies in South Asia, as well as emerging scholars who address new topics, this book decisively positions television as a key site in the study of South Asian History and Culture. In doing so, it also positions the study of television in South Asia and the South Asian diaspora as crucial in the rethinking of global television history and opens up new directions for the future of television studies. This volume will be essential reading for scholars and teachers of media and communication studies, media history, anthropology, and sociology, besides being of great interest to policymakers and media professionals.
Keywords: Television-Social aspects